Applications and challenges of hyperspectral remote sensing in the colombian geology (2015)
Remote Sensing (RS) is a data acquisition technique that requires no physical contact with the scene, through the use of sensors on aerial platforms. These sensors capture information in the electromagnetic spectrum different ranges, including the visible ones (VIS), the near infrared (NIR) and short wave range infrared (SWIR). Taking into account that each material present in a scene has different spectral characteristics, it is possible to analyze the spectral signatures and to use their identification and/or classification algorithms. Hyperspectral Image (HSI) remotely sensed in hundreds of spectral bands. HSI is important in different areas such as geology, mineralogy, agronomy, geography, environment, among others. However, the high volume of literature spread into different lines (RS, HSI and geology) makes it difficult to access and analyze it.This paper presents a summary of concepts, principles, and mathematical foundations, including RS research and trends, highlighting its development and challenges in Colombia, and a HSI case use in the Colombian geology, which shows the detection capability of the Hyperion hyperspectral sensor, located in the EQ-1 Satellite for geological mapping, in a test site, at the Girón town northwest of the Santander, Colombia. The results of these evaluations are correlated with the geological information obtained by analysis of X-ray diffraction (XRD), performed on the samples taken from the studied area.